Bibliometric Analysis of Financial Indicator Changes in the Banking Sector - Hawik, Hawik Ervina Indiworo (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze changes in banking financial indicators before and during the Covid-19 pandemic using a bibliometric approach. The data used in this study consists of 200 journals, with 45 journals meeting the relevance criteria, analyzed using VOSviewer software through three main visualizations: network visualization, overlay visualization, and density visualization. This study highlights the critical role of credit risk management and liquidity during the pandemic, as well as the importance of profitability performance recovery in the post-pandemic period. The findings provide insights into the trends and developments in banking sector research within the context of global economic changes.